A Dual-Polarized Stacked Ceramic Antenna With High Isolation - Liyuan Cao; Wenjian Sun; Hang Wong (IEEE Access)
In this work, two identical ceramic plates formed a stacked dense dielectric patch antenna is introduced for implementing a dual-polarized antenna. The proposed stacked ceramic structure generates highly pure adjacent modes, achieving wide impedance bandwidth, high isolation, and stable radiation performance across the entire operating bandwidth. The antenna combines with the advantages of the dense dielectric patch antenna and dielectric resonator antenna to produce symmetrical field distributions without spurious waves on the antenna body, resulting in high purities of radiation and polarization. A prototype of the proposed antenna is fabricated and tested. Its measured and simulated results are in good agreement. The 42% operating bandwidth covers from 3.3 GHz to 5.15 GHz for the reflection coefficient $\le $ -10 dB and with high isolation across the entire operating bandwidth. With the merits of low profile, wide bandwidth, high isolation and stable radiation performance, the proposed dual-polarized stacked ceramic antenna is promising for 5G/B5G wireless communication system.